EVALUATION AND ANALYSIS OF THE DEVELOPMENT STAGES OF BRAZILIAN STARTUPS - Lavezo dos Reis, Beatriz; Julia Cristina Bogoni, (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2026)
In an innovation-driven environment filled with uncertainties and challenges, it is essential to understand and delve into the culture and strategies of startups. In this context, the objective of this study is to assess the development stages of Brazilian startups through a questionnaire based on four constructs: management, leadership and culture, agility and product strategy, and business strategy. After a literature review and a survey of similar studies, a questionnaire was developed using the survey methodology and applied to 68 startups, covering companies from 11 different Brazilian states. Based on the results, actions and strategies were proposed to guide startups in the scale and traction maturity stages. The developed questionnaire is unique, as it builds upon previous studies while also incorporating original questions. This study stands out as the first to evaluate startups based on the four constructs collectively, providing valuable insights for those in the traction and scale stages. Among the key findings, differences in perspectives between the traction and scale stages were identified, as well as variations across different hierarchical levels within startups. Furthermore, opportunities for improvement in knowledge and innovation management within the organizational context were observed. Methodologically, this study proposes and validates a method for assessing startup maturity across multiple dimensions, which can be replicated by other researchers. Additionally, the study presents an overview of the startup ecosystem in Brazil and provides strategic guidelines to support startup decision-makers.